Waris Dan Wasiat Dalam Hukum Islam : Studi Atas Pemikiran Hazairin Dan Munawir Sjadzali - Muchammad Hammad (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2015)
This research is the study of thought, which compares between Hazairin idea and Munawir Sjadzali about inheritance and wills in Islamic Law. In contrast to the view of the majority of Muslim jurists, Hazarin and Sjadzali stated that the Islamic inheritance system in individual bilateral, as will the researchers describe in this paper. Researchers also will explain the differences in approach between the two figures is the originator of Indonesian schools of jurisprudence. Finally, it can be seen that both Hazarin and Sjadzali want any part of the waris and wasiat between male and female.